2021
DOI: 10.1159/000519418
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Sleep Duration and Screen Time with Incidence of Overweight in European Children: The IDEFICS/I.Family Cohort

Abstract: <b><i>Introduction:</i></b> Over the past decades, children have been increasingly using screen devices, while at the same time their sleep duration has decreased. Both behaviors have been associated with excess weight, and it is possible they act as mutually reinforcing behaviors for weight gain. The aim of the study was to explore independent, prospective associations of screen time and sleep duration with incident overweight in a sample of European children. <b><i>Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…Around the world, children were enrolled in school virtually, extracurricular activities were limited, and daily routines were adjusted to decrease the potential exposure to COVID-19. Potential consequences include increased screen time, unhealthy eating habits, decreased physical activity, and worsened sleep hygiene, all of which have associations with increased BMI [ 15 , 16 ]. A recent meta-analysis showed an increase in BMI in school-age children and an increase in obesity prevalence from 10.5% to 12.6% in high school and college students during the pandemic [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Around the world, children were enrolled in school virtually, extracurricular activities were limited, and daily routines were adjusted to decrease the potential exposure to COVID-19. Potential consequences include increased screen time, unhealthy eating habits, decreased physical activity, and worsened sleep hygiene, all of which have associations with increased BMI [ 15 , 16 ]. A recent meta-analysis showed an increase in BMI in school-age children and an increase in obesity prevalence from 10.5% to 12.6% in high school and college students during the pandemic [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Across the globe, children were enrolled in school virtually, extracurricular activities were limited, and daily routines were adjusted to decrease the potential exposure to COVID-19. Consequences of this included increased screen time, unhealthy eating habits, decreased physical activity, and worsened sleep hygiene, which all have associations with increased body mass index (BMI) [ 15 , 16 ].…”
mentioning
confidence: 99%
“…A growing body of evidence suggests that excessive screen time and early screen exposure have detrimental impacts on children [5][6][7][8][9]. For example, a multi-country cohort study has revealed a link between excessive screen time and an increased risk of overweight or obesity in children aged between 2 and 11 years [5].…”
Section: Introductionmentioning
confidence: 99%
“…We found that sleep duration and AVM possibly causally affect insulin resistance (HOMA), which in turn causally affects BMI. Others also reported associations of media exposure [32][33][34][35] and sleep 36,37 with insulin resistance, although the direction of the relationship between sleep and HOMA was inconsistent 38 . Although we found no clear evidence for a causal impact of physical activity, healthy diet or well-being on obesity, associations were previously found in the IDEFICS/I.Family cohort e.g.…”
Section: Discussionmentioning
confidence: 99%